Phylogeny and diversity of Rigidoporus (Hymenochaetales, Basidiomycota), including three new species from Asia - Wang, Chao-Ge; Vlasák, Josef; Jin, Can; Si, Jing (Frontiers in Cellular and Infection Microbiology, 2023)
Phylogenetic and morphological analyses on Rigidoporus were carried out. The genus Rigidoporus (Hymenochaetales, Basidiomycota), typified by R. microporus (Fr.) Overeem. (synonym Polyporus micromegas Mont.), was established by Murrill in 1905. The genus is mainly characterized by annual to perennial, resupinate, effused-reflexed to pileate or stipitate basidiomata with azonate or concentrically zonate and sulcate upper surface, a monomitic to pseudo-dimitic hyphal structure, simple-septate generative hyphae, and ellipsoid to globose basidiospores. Phylogeny on species of the genus is reconstructed with two loci DNA sequences including the internal transcribed spacer regions and the large subunit. Three new species in Rigidoporus are described and illustrated from Asia, and one new combination in the genus is proposed. The main morphological characteristics of the currently accepted species of Rigidoporus are provided.